Diferença entre características na formação do preço de venda e locação de imóveis na cidade de Vitória/ES - Lopes, Claudio Imperial (2015)
This dissertation studies the relevant features in the formation of sale and rental price, also analyzing the differences between these attributes for apartments in the city of Vitória/ES, filling a gap not yet developed, considering the possibility to compare rental and sale prices. The theoretical construct was based in the hedonic pricing approach, applied in studies of Waugh (1928) and Court (1939), but formally theoretically developed by Lancaster (1966) and Rosen (1974), and applied and discussed by Palmquist (1984) and Sheppard (1999). The literature review shows that there impacts related with physical aspects of the property, such as another’s related with external features, such as violence, easy access, or the presence of railway stations or markets nearby, among others. The sample came from a real estate supply list in the Netimóveis site during the months of May and June 2014, with a number of 563 observations for sale and 185 for rent. Besides these two samples, analyzes were prepared with respect to sub-samples that had the variable value of the condominium, seeking to expand the explanatory variables collected. The analysis was made using descriptive statistics, correlation between variables and multiple regressions, the latter being applied to the six proposed models for each sample, then proposing a final model for sale and rent. Regarding the assumptions used and applied in the models, some of which were used with a base previous study, and others, like the morning sun, for example, they were presented as proposals. About the results founded, many corroborated with previous studies, confirming that variables such as area, parking spaces, balcony, walk and drive forward position, swimming pool and located in affluent neighborhoods positively impact the price of real estate, regardless of whether sale or rent. How different it was possible to identify the variables presence of a lift, playground and value of the condominium participate positively the selling price of explanation, while the presence of court, furniture and morning sun positively explain the rent in the sample.